2018
DOI: 10.1039/c7ra12815k
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29c inhibits HCV replicationviaactivation of type I IFN response by targeting STAT3 in JFH-1-infected Huh7 cells

Abstract: MiR-29c, a member of the miR-29 family, has been recognized to play an important role in hepatitis C virus (HCV) infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The result suggested that STAT3 is involved in the development of cholesteatoma, and it was indicative of the high proliferation of the cholesteatoma epithelium. Meanwhile, various studies have shown that STAT3 is epigenetically regulated by miRNAs [ 34 , 35 ]. The results of statistical analysis of correlation showed that miR-125b and STAT3 were negatively correlated in cholesteatoma ( Figure 1 E ).…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested that STAT3 is involved in the development of cholesteatoma, and it was indicative of the high proliferation of the cholesteatoma epithelium. Meanwhile, various studies have shown that STAT3 is epigenetically regulated by miRNAs [ 34 , 35 ]. The results of statistical analysis of correlation showed that miR-125b and STAT3 were negatively correlated in cholesteatoma ( Figure 1 E ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with HIV/HCV co-infection, a down-regulation of serum levels of miR-29a was shown when compared to healthy control group and patients with HIV infection [ 59 ]. In vitro, HCV decreases the expression of miR-29 activating HSCs and miR-29c has been shown to repress HCV replication targeting STAT3 and induce the production of IFN I [ 96 , 97 ].…”
Section: Mirnas Expression During Chb and Chc Related Fibrosismentioning
confidence: 99%
“…It has been found that miR-221 was able to enhance IFNα's anti-HCV effect through SOCS1 and SOCS3 targeting [74]. miR-29c appeared to be protective against HCV infection by its effect on enhancing the STAT3-mediated type I IFN response in Huh7 cells [75]. miR-29 suppresses the immune response to intracellular bacterial infection by targeting IFN-γ [76].…”
Section: Discussionmentioning
confidence: 99%